KOMITMEN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA KARAKTER SISWA MELALUI KEGIATAN KEAGAMAAN PADA SEKOLAH MENENGAH PERTAMA NEGERI 21 BATANG HARI - Roihan, Muhammad; Syahran, M.; Rasidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education has become one of the primary priorities in Indonesian education to develop students who possess not only academic competence but also strong moral and religious values. However, the effectiveness of character development is highly influenced by teachers' commitment in implementing sustainable educational programs. This study aims to analyze the commitment of Islamic Religious Education (PAI) teachers in fostering students' character through religious activities at SMP Negeri 21 Batang Hari. The research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, Islamic Religious Education teachers, several teachers, and students selected using purposive sampling. Data were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the commitment of Islamic Religious Education teachers plays a significant role in strengthening students' religious, disciplinary, responsible, polite, honest, and socially caring character through various religious activities, including congregational prayers, Qur'an recitation, Yasin recitation, Friday charity programs, religious lectures, and Islamic boarding school activities during Ramadan. Teachers demonstrated their commitment by actively planning, implementing, supervising, mentoring, evaluating, and serving as role models throughout the character-building process. Although several obstacles were identified, including students' low motivation, family support, and peer influence, these challenges were addressed through continuous habituation, individual guidance, exemplary behavior, and collaboration with parents. Therefore, teachers' commitment serves as the key factor in ensuring the successful implementation of character education through religious activities in schools.